INFRASTRUKTUR TEKNOLOGI INFORMASI PADA GERAI ALFAMART SUKARAMI PALEMBANG - Fenny Purwani; Erin Aryanti; Faza Intaniansyah; Dina Olyvia; Almahira Mutia Zakia (Jurnal Riset Sistem Informasi, 2025)
This study aims to analyze the implementation of information technology infrastructure at the Alfamart Sukarami Palembang branch, identify the main components of IT infrastructure used, and describe the challenges and obstacles faced in its management. Utilizing a descriptive qualitative research method, data were collected through direct observation at the store and secondary data analysis from various reliable sources. The results indicate that Alfamart has implemented an integrated IT infrastructure, including hardware (cash registers, barcode scanners), software (internal retail systems), communication networks (VPN, intranet), data centers, information security systems, and cloud computing technology. This infrastructure supports operational efficiency, transaction service speed, and data management accuracy. Based on SWOT analysis, Alfamart possesses strengths in providing facilities and customer-friendly services, but faces challenges such as intense competition and obstacles in goods distribution. This study recommends enhancing IT infrastructure, employee training, increased promotion, regular system evaluation, and maximizing the use of cloud technology to improve Alfamart’s competitiveness in the modern retail industry.